2015
DOI: 10.1016/j.seizure.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and outcome of generalized convulsive status epilepticus in elderly

Abstract: Less than one-third of elderly patients with CSE progressed to RSE. Vascular aetiology, the leading cause of generalized CSE in elderly, was not associated with progression to RSE and mortality. Acute symptomatic aetiology was associated with high mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…Yoshimura et al reported that poor outcome was associated with acute symptomatic (p = 0.003) and remote symptomatic (p = 0.02) compared with cryptogenic SE [22]. In our study, only acute symptomatic SE was associated with poor outcome, which is in concordance with few reports [4,24]. Treiman et al reported that the 30-day mortality was 27% and unresponsiveness to the first AED was the most significant risk factor [13].…”
Section: Discussionsupporting
confidence: 91%
“…Yoshimura et al reported that poor outcome was associated with acute symptomatic (p = 0.003) and remote symptomatic (p = 0.02) compared with cryptogenic SE [22]. In our study, only acute symptomatic SE was associated with poor outcome, which is in concordance with few reports [4,24]. Treiman et al reported that the 30-day mortality was 27% and unresponsiveness to the first AED was the most significant risk factor [13].…”
Section: Discussionsupporting
confidence: 91%
“…Whereas the mortality rate is about 13% in young adults, it reaches 38% in older adults of 60–79 years old, and was found up to 50% after 80 years [ 17 ]. Regarding severity of status epilepticus, mortality has been demonstrated as higher in patients with refractory status epilepticus [ 18 ] or super refractory status epilepticus aged over 75 years [ 19 ]. Independent predictors of mortality are also particularly marked by age since 65 years old has been identified as a fatal cut off value in several studies [ 17 , 18 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding severity of status epilepticus, mortality has been demonstrated as higher in patients with refractory status epilepticus [ 18 ] or super refractory status epilepticus aged over 75 years [ 19 ]. Independent predictors of mortality are also particularly marked by age since 65 years old has been identified as a fatal cut off value in several studies [ 17 , 18 , 20 , 21 , 22 , 23 ]. Others factors associated with hospital mortality are related to seizure duration, an underlying CNS structural lesion, de novo status epilepticus, intensity of consciousness disorders at scene and refractory status epilepticus [ 20 , 21 , 22 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Higher mortality in older adults also contrasts to the less than 5% mortality among younger adults well into the fourth decade of life [11,16]. Previously, among older adults, the overall mortality rates with SE in hospital-based studies have ranged from 6.5% to 31% [5,6,7,8,9,10,11]. However, in contrast to our study in older adults, these prior investigations among older adults were limited by being single center studies, primarily done outside the United States, and with very small sample sizes (range of 33 to 140 subjects) [5,6,7,8,9,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies indicate that older adults have an increased propensity for SE and associated higher mortality [3,4]. However, hospital-based studies in older adults are limited by their small sample size from single institutional studies [5,6,7,8,9,10,11]. Others included an all adult population [12] or were focused on specific subgroup etiologies [13].…”
Section: Introductionmentioning
confidence: 99%